Effect of forced cooling on the microstructure and properties of Fe-based amorphous composite coatings prepared by laser remelting. (June 2022) - Zhao, Wei; Yu, Jiacheng; Hu, Mindong; Hu, Honglei; Luo, Junting
Abstract: A forced cooling system with three cooling plates was designed to assist laser remelting, and the effects of forced cooling on the microstructure and properties of Fe-based amorphous composite coatings prepared by laser remelting were studied. Results show that the content and size of the precipitated crystalline phase decrease, and the crystallites become finer with an increase in the temperature gradient of the forced cooling device. When the temperature of the cooling plate drops to 200 K, the precipitation of the strengthening phase M23 (CB)6 is inhibited, and only the α-Fe phase precipitates, which has a good toughening effect. The hardness of the coating decreases because the precipitation of the strengthening phase is inhibited. The wear and corrosion resistances of the coatings are significantly improved because of an increase in the content of the amorphous phase and solid solution strengthening of the α-Fe phase. However, lowering the temperature of the cooling plate does not result in better performance. At a cooling plate temperature of 200 K, the wear resistance of the coating is the best because the appropriate amount of α-Fe phase plays a toughening effect. Highlights: A forced cooling system was designed to assist laser remelting. Forced cooling can restrain the precipitation of crystallized phase in the coatings. When the cooling plate temperature drops to 200 K, only α-Fe phase precipitates. Forced cooling improves the wear resistance and corrosion resistance of the coating. Appropriate amount of α-Fe phase can toughen the coating.